2016
DOI: 10.1016/j.bjm.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of aminoglycoside-modifying enzyme and virulence genes among enterococci with high-level aminoglycoside resistance in Inner Mongolia, China

Abstract: This study highlights the prevalence of aminoglycoside-modifying enzyme genes and virulence determinants among clinical enterococci with high-level aminoglycoside resistance in Inner Mongolia, China. Screening for high-level aminoglycoside resistance against 117 enterococcal clinical isolates was performed using the agar-screening method. Out of the 117 enterococcal isolates, 46 were selected for further detection and determination of the distribution of aminoglycoside-modifying enzyme-encoding genes and virul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 30 publications
7
16
3
2
Order By: Relevance
“…In various studies, similar frequencies of the efa have been reported [489]. In a study conducted by Gaglio et al, the efa gene was detected among 25% of the strains isolated from dairy products [19].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In various studies, similar frequencies of the efa have been reported [489]. In a study conducted by Gaglio et al, the efa gene was detected among 25% of the strains isolated from dairy products [19].…”
Section: Discussionsupporting
confidence: 53%
“…Our results indicated that E. faecalis isolates carried more virulence genes in comparison to various reports [49181925262728]. These differences probably reflect variability in the types of samples or geographic regions.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…Previous studies by Padmasini et al [11], Bhatt et al [16], and Niu et al [17] have reported that HLGR (42.7%, 65%, and 42.7%) was more common than HLSR (29.8%, 45%, and 27.4%) in all species of isolated enterococci respectively. On the contrary, there was nearly no difference between the prevalence rates of HLGR and HLSR among our studied Enterococcus species isolates.…”
Section: Discussionmentioning
confidence: 84%